A biomimetic approach to improving tribological properties of hybrid PTFE/Nomex fabric/phenolic composites. (May 2016) - Yang, Mingming; Yuan, Junya; Guo, Fang; Wang, Kun; Zhang, Zhaozhu; Men, Xuehu; Liu, Weimin
Graphical abstract: Highlights: Dopamine was employed to modify GO, MWCNTs, and hybrid PTFE/Nomex fabric. Interfacial strength and dispersion of GO, MWCNTs greatly improved after modified by dopamine. The tribological performances of hybrid PTFE/Nomex fabric composite significantly enhanced. Abstract: Interfacial strength between reinforcement and polymer matrix and dispersion of lubricant fillers in polymer composites are vital properties in determining the mechanical behaviors and tribological performance. In this work, a facile biomimetic method was employed to improve the interfacial strength between hybrid PTFE/Nomex fabric and phenolic resin as well as the dispersion of carbon carbonaceous in phenolic composite. Dopamine is the main component of mussel adhesive proteins which can easily attach on substrate surface by self-polymerization under weak basic buffer solution. Hence, polydopamine modified graphene oxide (D-rGO) and multi-walled carbon nanotubes (D-MWCNTs) were incorporated into polydopamine functionalized hybrid PTFE/Nomex fabric (D-fabric) composite to improve the tribological performance of the phenolic composite. XPS, TGA, SEM, and TEM characteristics illustrated that the hybrid PTFE/Nomex fabric, graphene oxide (GO), and carbon nanotube (MWCNTs) were successfully functionalized by polydopamine. More importantly, wear test results showed that D-rGO (or D-MWCNTs) reinforced D-fabric phenolic composite exhibited excellent tribological performance. The wear test results and corresponding wear mechanisms of the hybrid PTFE/Nomex fabric composite were discussed in terms of characterizations.